Educational Response Offered by the State of Chile to Young Offenders. A Perspective from the Declared Curriculum and the Educational Practices of a Provisional Internment Center in a Closed Regime - Dominguez, Julio; Sanhueza, Suan; Puentes, Daniela; Maldonado, Fabiola; Aroca, Carolina; Rodriguez, Gabriel; Mejias, Jaime (Journal of Ecohumanism, 2024)
The objective of the study was to analyze the educational response offered by the State and binding educational institutions such as SENAME to young offenders in closed regime. A case study, with a qualitative approach, interviewing six young people (2 women and 4 men) between 14 and 20 years old, whose sentences range from 2 to 10 years. The interviews are complemented by stories from families and professionals in charge of the center. The results show an education focused on job skills, and a rigid and technical curriculum not adjusted to the characteristics of the young people. The evaluation represents a critical knot for the professional team, since it focuses on institutional requirements in terms of indicators and results.